Proceedings 22nd IEEE Real-Time Systems Symposium (RTSS 2001) (Cat. No.01PR1420)
DOI: 10.1109/real.2001.990610
|View full text |Cite
|
Sign up to set email alerts
|

Static-priority scheduling on multiprocessors

Abstract: The preemptive scheduling of systems of periodic tasks on a platform comprised of several identical processors is considered. A scheduling algorithm is proposed for staticpriority scheduling of such systems; this algorithm is a simple extension of the uniprocessor rate-tnonotonic scheduling algorithm. It is proven that this algorithm successfully schedules any periodic task system with a worst-case utilization no more than a third the capacity of the multiprocessorplatform. It is also shown that no static-prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
215
0
5

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(220 citation statements)
references
References 17 publications
0
215
0
5
Order By: Relevance
“…For global RM scheduling, system utilization of (m/2)(1 − α) + α can be guaranteed [5]. Andersson et al also studied one scheduling algorithm named RM-US, where tasks with utilizations higher than some threshold θ have the highest priority [3]. For θ = 1 3 , Baker showed that RM-US can guarantee a system utilization of (m + 1)/3 [5].…”
Section: Related Workmentioning
confidence: 99%
“…For global RM scheduling, system utilization of (m/2)(1 − α) + α can be guaranteed [5]. Andersson et al also studied one scheduling algorithm named RM-US, where tasks with utilizations higher than some threshold θ have the highest priority [3]. For θ = 1 3 , Baker showed that RM-US can guarantee a system utilization of (m + 1)/3 [5].…”
Section: Related Workmentioning
confidence: 99%
“…Some multiprocessor studies in the past (e.g., Andersson et al 2001;Cho et al 2002;Srinivasan and Baruah 2002) have focused on adapting existing uniprocessor scheduling to multiprocessors, and some others have developed novel policies specific to multiprocessors (e.g., Baruah et al 1996;Anderson and Srinivasan 2000;Cho et al 2006;Andersson and Tovar 2006;Funaoka et al 2008;Easwaran et al 2009;Levin et al 2010). In spite of some significant achievements of these studies, many important scheduling problems continue to pose challenges including the efficient scheduling of general task systems such as those in which task deadlines differ from their periods.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for global-RMS scheduling, a system utilization of (m/2)(1 − α) + α can be guaranteed (Baker 2003). Andersson et al also studied the scheduling algorithm RM-US, where tasks with utilization higher than some threshold θ have the highest priority (Andersson et al 2001). For θ = 1 3 , Baker showed that RM-US can guarantee a system utilization of (m + 1)/3 (Baker 2003).…”
Section: Related Workmentioning
confidence: 99%
“…Despite its flexibility that allows tasks to migrate and execute on different processors, it has been shown that simple global scheduling policies (e.g., global-EDF and global-RMS) could fail to schedule task sets with very low system utilization (Dhall and Liu 1978). For task sets where the maximum task utilization is limited, some utilization bounds have also been studied for global-EDF and global-RMS scheduling algorithms (Andersson et al 2001;Baker 2003;Goossens et al 2003).…”
Section: Introductionmentioning
confidence: 99%